A dataset of factors that influence preservice teachers' intentions to use Web 2.0 technologies in future teaching practices - Yusop, F.D. (Blackwell Publishing, 2015)
In recent years, researchers have focused on investigating factors that influence preservice teachers' utilization of Web 2.0 technologies in their classrooms. Findings indicate that preservice teachers' intentions, beliefs and attitudes toward technology are important determinants of the success of future technology integration. However, studies tracking the impact of Web 2.0 training on preservice teachers' intentions are still lacking. Moreover, publicly available datasets on the topic are still very limited. This paper presents a dataset of various independent and dependent variables that may influence preservice teachers' intentions to use Web 2.0 technologies in their future teaching practices. A questionnaire modified to conform to the theory of planned behavior (TPB) was distributed to 100 preservice teachers at a public university in Malaysia. The resulting dataset should be beneficial to preservice teacher educators in designing effective training that best nurtures future preservice teachers' familiarity and intentions to utilize Web 2.0 technologies. Interested researchers sharing similar sample characteristics may also utilize this dataset to conduct more rigorous statistical analyses.